2009
DOI: 10.1212/wnl.0b013e3181c0d454
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal correlates of pain in healthy elderly adults

Abstract: Older adults who report more severe acute or chronic pain have smaller hippocampal volumes and lower levels of hippocampal N-acetylaspartate/creatine, a marker of neuronal integrity. Future studies should consider the role of the hippocampus and other brain structures in the development and experience of pain in healthy elderly and individuals with Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…Poor sleep seems to reduce pain threshold and predispose to chronic pain, which may worsen sleep quality (Finan, et al, 2013). Akin to our findings in fatigue patients, hippocampal volume reduction has been reported in healthy elderly adults with increased pain duration and intensity (Zimmerman, et al, 2009). Primarily frontal cortical thickness (Chen, et al, 2016) and fronto-temporal GMV (Zhang, et al, 2013) reduction has also been described in chronic obstructive pulmonary disease.…”
Section: Discussionsupporting
confidence: 88%
“…Poor sleep seems to reduce pain threshold and predispose to chronic pain, which may worsen sleep quality (Finan, et al, 2013). Akin to our findings in fatigue patients, hippocampal volume reduction has been reported in healthy elderly adults with increased pain duration and intensity (Zimmerman, et al, 2009). Primarily frontal cortical thickness (Chen, et al, 2016) and fronto-temporal GMV (Zhang, et al, 2013) reduction has also been described in chronic obstructive pulmonary disease.…”
Section: Discussionsupporting
confidence: 88%
“…Plasticity of hippocampal volume is also observed across a number of conditions including: (1) decreased volume in Alzheimer’s disease (Devanand et al 2007); major depression (Sheline 2003); Cushing’s disease (Starkman et al 1999); PTSD (Woon et al 2010); schizophrenia (Koolschijn et al 2010); a 20-year history of chronic perceived stress (Gianaros et al 2007); chronic inflammation (Marsland et al 2008); jet lag (Cho 2001); and acute, or as noted above, in chronic pain (Zimmerman et al 2009); (2) increased volume is observed after electroconvulsive therapy (Nordanskog et al 2010) and sustained, moderate exercise (Erickson et al 2011); and (3) vary in volume in the rostrocaudal extent of the structure with acquisition of special skills (Hufner et al 2010). Thus, our observation of altered volume in the hippocampus, while not new in central nervous system (CNS) diseases and after chronic stress conditions, is new in the context of migraine and in the context of migraine frequency.…”
Section: Discussionmentioning
confidence: 97%
“…Many investigators have evaluated the role of the hippocampus in pain processing in human and animal studies (Bingel et al, 2002; Duric and McCarson, 2006; Schweinhardt et al, 2006; Zimmerman et al, 2009). Neuroimaging studies have shown that the hippocampus is activated in response to painful stimuli in healthy volunteers (Bingel et al, 2002).…”
Section: Inroductionmentioning
confidence: 99%
“…Furthermore, adults with chronic pain syndromes have functional and anatomical alterations in brain regions involved in pain processing including the hippocampus, the thalamus, the basal ganglia and amygdala as well as cingulate, prefrontal and somatosensory cortex (Schweinhardt and Bushnell, 2010). In older adults, higher levels of pain severity have been associated with both reductions in hippocampal volume (HV) and lower NAA levels in the hippocampus (Zimmerman et al, 2009). Alterations in specific transmitters have been demonstrated.…”
Section: Inroductionmentioning
confidence: 99%